The National Institute of Medical Sciences and Nutrition Salvador Zubirán: A Brief Journey Through its History - David Kershenobich-Stalnikowitz (Permanyer, 2021)
The National Institute of Medical Sciences and Nutrition Salvador Zubirán (INCMNSZ) is an institution of reference in health that provides specialized medical attention in adults, training of human resources, and research, with an integral approach and excellency for the benefit of human beings and their environment (Table 1).